Ichthyofauna of Santa Helena Relevant Ecological Interest Area (REIA), Paraná, Brazil - Brandão, Heleno (2022)
The Relevant Ecological Interest Area (REIA), popularly known as “Refúgio Biológico de Santa Helena”, is part of the Atlantic Forest Biome and one of the 78 ecoregions mapped by IBAMA as basic unit for planning priorities focused on national biodiversity conservation. Quarterly collections were carried out from November 2017 to November 2019 to inventory the ichthyofauna of this Conservation Unit. Specimens were captured with the aid of gillnets, fishing sieve and seine. In total, 3,919 specimens belonging to two class, eight orders, 27 families and 74 species were sampled. Characiformes and Siluriformes presented the highest species richness; they accounted for 40 (54%) and 17 (23%) species, respectively. Geophagus sveni (181 individuals = 17%), Trachelyopterus galeatus (109 individuals = 10%) and Schizodon borellii (105 individuals = 10%) were the most abundant fish species captured with gillnet. Moenkhausia was the most abundant genus captured with seine and fishing sieve, with emphasis on species Moenkhausia bonita (930 individuals = 33%) and Moenkhausia gracilima (845 individuals = 30%). Moreover, two “endangered” species (Brycon orbignyanus and Pseudoplatystoma corruscans) were registered. Therefore, we present an updated inventory of species belonging to the ichthyofauna of REIA, and it may contribute to future management plans focused on this Conservation Unit.